The impact of digitalization towards the sustainability of Malaysian SMEs: the dynamic capabilities perspective - Abu Jaish, Anas Ahmad; Murdipi, Rafiqa; Abdul Razak, Dzuljastri; Mohd Alwi, Norhayati (Springer Nature, 2023)
In many developing countries SMEs is considered as one of the main contributors to their economies. However, Malaysian SMEs still face numerous challenges in all sectors. Uncertainties such as Covid-19 and digitalization are the main current uncertain issues in Malaysia. This paper examines the resource capabilities of Malaysian SMEs in handling uncertain environments by identifying the importance of digitalization in their efforts to maintain the sustainability of their market. The quantitative method was employed by using a questionnaire to collect data that represented the research objective. A preliminary study is conducted to test the reliability and validity of the questionnaire. The paper also discusses the preliminary data analysis and descriptive analysis of study variables. As a result, the researcher addressed the preliminary study findings accordingly. The study found that SMEs somehow agreed that business sustainability depends on the speed of responses towards environmental changes and digitalization are considered the long-term sustainable business plan. The study contributes to existing literatures as well as benefits both governmental and non-governmental institutions, policymakers, and agencies by providing crucial information which assists them to identify the proper plan and assistance for SMEs. The main concern for this study is to assist SMEs in being more stable and sustainable during the challenging uncertain market conditions.